1997
DOI: 10.1113/jphysiol.1997.sp021949
|View full text |Cite
|
Sign up to set email alerts
|

Renal handling of guanidino compounds in rat and rabbit.

Abstract: 1. Guanidino compounds (GCs) have been quantified in different mammalian tissues such as brain, liver, muscle and kidney. The high anatomical heterogeneity of the kidney suggests that GCs could be unevenly distributed along the corticopapillary axis of the kidney in different species. 2. This study was designed to quantify twelve GCs in the different zones of rat and rabbit kidney. The kidneys were sliced and pieces of seven definite zones were weighed and homogenized for further GC extraction. GCs were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Arg synthesis depends on the citrulline concentration, it requires aspartate and takes place essentially in the proximal convoluted tubules [13,25]. In kidneys, the highest level of Arg is located in the cortex followed by the outer stripe of the outer medulla -two zones where the proximal tubules lie [27]. In animals submitted to experimental nephrectomy, destroying the proximal tubules results in an enhancement of citrullinemia and an accumulation of citrulline in extra-renal organs in proportion to renal damage [8,28,49].…”
Section: Discussionmentioning
confidence: 99%
“…Arg synthesis depends on the citrulline concentration, it requires aspartate and takes place essentially in the proximal convoluted tubules [13,25]. In kidneys, the highest level of Arg is located in the cortex followed by the outer stripe of the outer medulla -two zones where the proximal tubules lie [27]. In animals submitted to experimental nephrectomy, destroying the proximal tubules results in an enhancement of citrullinemia and an accumulation of citrulline in extra-renal organs in proportion to renal damage [8,28,49].…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study [22,26], GAA was decreased in 24-h urine samples from uremic patients, since urine production would be impaired in a substantial portion of the kidney. It was reported that GSA and GAA are localized in the inner medulla and cortex of the kidney, respectively [27]. These observations possibly indicate that GSA is the first to increase as a urinary marker in the inner medulla, and that GSA promotes the production of NO via NMDA receptors [28,29].…”
Section: Application Datamentioning
confidence: 97%
“…Each of the natural GCs: Arg, GAA, guanidinosuccinic acid (GSA), CT, creatinine (CTN), homoarginine (HArg), α-N-acetylarginine (α-N-AA), β-guanidinopropionic acid (β-GPA), γ-guanidinobutyric acid (γ-GBA), α-keto-δ-guanidinovaleric acid (α-keto-δ-GVA), guanidine (G) and methylguanidine (MG) exhibit typical distribution patterns along the cortico-papillary axis [16]. Moreover, it is noteworthy that, in adult rats, the tissue concentrations of α-keto-δ-GVA, GSA, CTN, MG, α-N-AA and γ-GBA increase steeply from the inner stripe of the outer medulla to the papillary tip and, thus, constitute gradients which run in parallel to the well-known urea and osmotic gradients [26,31].…”
Section: Introductionmentioning
confidence: 99%
“…GCs have been localized within the mammalian kidney and are unevenly distributed along the cortico-papillary axis of the rat kidney [16]. Each of the natural GCs: Arg, GAA, guanidinosuccinic acid (GSA), CT, creatinine (CTN), homoarginine (HArg), α-N-acetylarginine (α-N-AA), β-guanidinopropionic acid (β-GPA), γ-guanidinobutyric acid (γ-GBA), α-keto-δ-guanidinovaleric acid (α-keto-δ-GVA), guanidine (G) and methylguanidine (MG) exhibit typical distribution patterns along the cortico-papillary axis [16].…”
Section: Introductionmentioning
confidence: 99%